2020
DOI: 10.3389/fcell.2020.587697
|View full text |Cite
|
Sign up to set email alerts
|

Stromal Expression of the Core Clock Gene Period 2 Is Essential for Tumor Initiation and Metastatic Colonization

Abstract: The circadian clock regulates diverse physiological processes by maintaining a 24-h gene expression pattern. Genetic and environmental cues that disrupt normal clock rhythms can lead to cancer, yet the extent to which this effect is controlled by the cancer cells versus non-malignant cells in the tumor microenvironment (TME) is not clear. Here we set out to address this question, by selective manipulation of circadian clock genes in the TME. In two different mouse models of cancer we find that expression of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 62 publications
0
13
0
Order By: Relevance
“…Similarly, by multi-omics computation techniques, several core circadian clock genes are found changed epigenetically in lung adenocarcinomas and lung squamous cell carcinomas, which are involved in cell cycle and apoptosis, such as PER2 and RORA ( Yang et al, 2019 ). By applying MC38, a colorectal cancer cell line, in a syngeneic mouse model of liver metastasis, Per1 –/– Per2 –/– mice had reduced liver metastasis, and Per2 –/– livers had less cancer-associated fibroblasts infiltration and collagen deposition ( Shaashua et al, 2020 ). Further characterizations revealed that stromal Per2 is also required for primary tumor formation ( Shaashua et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, by multi-omics computation techniques, several core circadian clock genes are found changed epigenetically in lung adenocarcinomas and lung squamous cell carcinomas, which are involved in cell cycle and apoptosis, such as PER2 and RORA ( Yang et al, 2019 ). By applying MC38, a colorectal cancer cell line, in a syngeneic mouse model of liver metastasis, Per1 –/– Per2 –/– mice had reduced liver metastasis, and Per2 –/– livers had less cancer-associated fibroblasts infiltration and collagen deposition ( Shaashua et al, 2020 ). Further characterizations revealed that stromal Per2 is also required for primary tumor formation ( Shaashua et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…By applying MC38, a colorectal cancer cell line, in a syngeneic mouse model of liver metastasis, Per1 –/– Per2 –/– mice had reduced liver metastasis, and Per2 –/– livers had less cancer-associated fibroblasts infiltration and collagen deposition ( Shaashua et al, 2020 ). Further characterizations revealed that stromal Per2 is also required for primary tumor formation ( Shaashua et al, 2020 ). This finding implies the importance of PER family genes in TME.…”
Section: Discussionmentioning
confidence: 99%
“… 33 Recently, it has been found that an imbalance in PER2 gene expression is associated with NSCLC, 12 ovarian cancer, pancreatic cancer, breast cancer, prostate cancer, thyroid cancer, and so on. 16 , 33 - 35 However, it has been reported that PER2 not only has anti-cancer effects in CRC but also has carcinogenic effects, 18 , 19 indicating that the expression of PER2 is controversial. The most important thing regarding PER2 is that the latest research shows that it is associated with the tumorigenesis and development of gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“… 12 , 13 , 15 - 18 Meantime, it is also discovered that PER2 in TME has unexpected tumorigenic effects in the liver metastasis model of colon cancer in mice. 19 So the expression of PER2 in CRC is controversial. Therefore, it is necessary to clarify the role of PER2 in CRC and the specific underlying molecular mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Sixty percent of all CRC cases arise from adenomatous polyps following the adenoma-carcinoma sequence (also named the conventional pathway) ( Lau et al, 2020 ; Shaashua et al, 2020 ). Wnt signaling is continuously activated in the intestinal organs of APC-deficient mice, which interferes with the differentiation process.…”
Section: Applications Of Ios According To the Four Clusters Of The Network Analysismentioning
confidence: 99%